ANALISIS HUBUNGAN TERAPI ANTIHIPERTENSI SEBAGAI PENCEGAHAN SEKUNDER TERHADAP KEJADIAN SERANGAN ULANG STROKE ISKEMIK PADA PASIEN STROKE ISKEMIK - Adnan adnan; susan fitria candradewi; Shinta Dewi Nur Rahmah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Individuals who survive a first ischemic stroke are at high risk for recurrent stroke. This study aims to analyze the relationship between antihypertensives on the incidence of ischemic stroke recurrence in ischemic stroke patients. Type of research is analytic observational with a retrospective cohort approach. The research sample was taken using purposive sampling technique. The research sample was patients who had an ischemic stroke at PKU Muhammadiyah Hospital Yogyakarta in 2018. There were 201 samples that met the inclusion criteria. Consisting of 135 treatment groups and 66 patients as the control group. In the treatment group, 110 patients did not have recurrent strokes and 25 patients had recurrent strokes. In the control group there were 58 patients who did not have recurrent strokes and 8 patients had recurrent strokes. Statistical analysis showed an RR value of 0.927 (95% CI: 0.822-1.046) and p-value of 0.344. The conclusion from the results of this study is that there is no relationship between the administration of antihypertensive therapy with the incidence of ischemic stroke recurrence in ischemic stroke patients at PKU Muhammadiyah Hospital Yogyakarta.